Frequency of the most common CYP3A5 polymorphisms in the healthy population of the Republic of Macedonia - Krume Jakovski; Aleksandra Kapedanovska Nestorovska; Nikola Labacevski; Aleksandar J. Dimovski (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
The genetic polymorphism affecting the CYP3A5 enzyme is responsible for inter-individual and interethnic variability in the metabolism of CYP3A5 substrates. The aim of this study was to analyze the distribution of the most common CYP3A5*3 allelic variants in the healthy population of R. Macedonia and to investigate if the allelic frequency falls within the assumed range for European Caucasians. The total of 174 healthy volunteers from the general population were included. The genotyping of the CYP3A5*3 variant alleles, *3A (rs15524) and *3E (rs28365095), was performed with Real-Time PCR based on the allelic discrimination method using a TaqMan SNP genotyping assay according to the manufacturer's instructions. The CYP3A5*3 allele is abundantly present displaying an allelic frequency of 0.922. We estimate that 0.82 of the Macedonian population are homozygotes for the variant and do not have a CYP3A5 enzymatic activity. Our study demonstrated a high prevalence of CYP3A5*3 allele in the Macedonian population. The distribution of CYP3A5 alleles was similar to that found in other European Caucasians. As the goals of personalized medicine are beginning to be realized, this provides basic information on the CYP3A5 allele frequency for the future pharmacogenetic research in R. Macedonia.